2015
DOI: 10.5433/1679-0359.2015v36n3p1467
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological aspects of feline leishmaniasis in Brazil

Abstract: Tegumentary and visceral leishmaniasis are severe and unfortunately common parasitic diseases in Brazil. Among domestic animals, dogs are considered the main urban reservoir of the protozoan parasites, however, there is evidence that infected cats can also contribute towards the disease pool. The number of cats diagnosed with leishmaniasis has greatly increased in the last few years, highlighting the importance of thorough investigations on the role of the cat in the epidemiological cycle of the disease and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 59 publications
0
21
0
10
Order By: Relevance
“…PCR is a technique that, when combined with other tests, becomes convenient for the detection of asymptomatic carriers of the parasite in endemic areas and for the evaluation of vectors and animal reservoirs involved in the cycle of leishmaniosis [50]. In the present study, the use of whole blood was shown to be more sensitive for the detection of Leishmania spp., with 9.1% (5/55) of positivity.…”
Section: Discussionmentioning
confidence: 70%
“…PCR is a technique that, when combined with other tests, becomes convenient for the detection of asymptomatic carriers of the parasite in endemic areas and for the evaluation of vectors and animal reservoirs involved in the cycle of leishmaniosis [50]. In the present study, the use of whole blood was shown to be more sensitive for the detection of Leishmania spp., with 9.1% (5/55) of positivity.…”
Section: Discussionmentioning
confidence: 70%
“…Although domestic cats are relatively resistant to Leishmania infection (Solano-Gallego et al, 2007), clinical signs including cutaneous ulcerated lesions, nodular dermatitis and alopecia (Mancianti et al, 2004;Silveira et al, 2015) may occur in a small number of infected animals.…”
Section: Introductionmentioning
confidence: 98%
“…showing antibody titers much lower (below 1:80) than canine leishmaniosis (CanL) (Gramiccia, 2011;Silveira Neto et al, 2015). Therefore, PCR assays are considered to be more sensitive than serology to diagnose leishmaniosis in cats (Martin-Sanchez et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last two decades, there has been a considerable increase in epidemiological studies and reports of FeL, especially in areas endemic for canine and human leishmaniasis (PENNISI et al, 2015). However, there is limited knowledge about its immunological and pathophysiological aspects, making the diagnosis challenging (SILVEIRA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%